(p,q)-Growth of an Entire GASHE Function and the Coefficient βn = |an|/Γ(n+μ+1) - Mohammed Harfaoui; Abdellah Mourassil; Loubna Lakhmaili (International Journal of Mathematics and Mathematical Sciences)
The main purpose of this paper is to extend the work concerning the measures of growth of an entire function solution of the generalized axially symmetric Helmholtz equation ∂2u/∂x2+∂2u/∂y2+(2μ/y)(∂u/∂y)=0,  μ>0, by studying the general measures of growth ((p,q)-order, lower (p,q)-order, (p,q)-type, and lower (p,q)-type) in terms of coefficients |an|/Γ(n+μ+1) and the ratios of these successive coefficients.